Behçet’s Disease—Do Microbiomes and Genetics Collaborate in Pathogenesis? - Mehmood, Nafeesa; Low, Liying; Wallace, Graham R. (Frontiers in Immunology, 2021)
Behcet's disease (BD is a multisystem autoiinflammatory condition characterised by mucosal ulceration, breakdown of immune privilege sites and vasculitis. A genetic basis for BD has been descried in genome-wide and validation studies. Similarly, dysbiosis of oral and gut microbiomes have been associated with BD. This review will describe links between genetic polymorphisms in genes encoding molecules involved in gut biology and changes seen in microbiome studies.. A potential decrease in bacterial species producing short chain fatty acids linked to mutations in genes involved in their production suggests a potential therapy for BD.